Medial gastrocnemius muscle volume in ambulant children with unilateral and bilateral cerebral palsy aged 2 to 9 years - Barber, L.; Read, F.; Lovatt Stern, J.; Lichtwark, G.; Boyd, Roslyn (Wiley-Blackwell Publishing Ltd., 2016)
Aim: Calf muscle growth in children with unilateral cerebral palsy (UCP) and bilateral cerebral palsy (BCP) is unknown. This cross-sectional study examines the medial gastrocnemius growth rates of ambulatory children with UCP and BCP compared with children with typical development (CTD), aged 2 to 9 years. Method: Fifty children with UCP (mean age 66mo [SD 18], 29 males, Gross Motor Function Classification System [GMFCS] I=32, II=18), 50 children with BCP (age 64mo [SD 19], 31 males, GMFCS I=21, II=29), and 78 CTD (age 64mo [SD 16], 40 males) participated in the study. The medial gastrocnemius muscle volume was measured at rest using a validated freehand three-dimensional (3D) ultrasound method. Results: Normalized medial gastrocnemius muscle growth rate was significantly less in the children with UCP (0.001 mL/kg/mo) compared with the BCP (0.015 mL/kg/mo, p=0.001) and CTD (0.014 mL/kg/mo, p<0.001) groups. Normalized medial gastrocnemius muscle growth rate was the same in the BCP and CTD groups (p=0.77). Interpretation: The normalized growth rate of the medial gastrocnemius muscle in children aged 2 to 9 years with UCP is significantly lower compared with children with BCP and CTD. The growth rate differences in the children with UCP compared with BCP raises questions about the underlying mechanisms that lead to reduced growth in each cerebral palsy (CP) group and potential differences in muscle recovery response in UCP and BCP following treatment.